Leonardo da vinci: Precursor de la epistemología moderna1 (2018)
Presents a portrait of the scientific life of the great genius of the Renaissance and reveals his epistemological work. The clear intention of this article is to highlight that the epistemology of Leonardo is unknown by modernity, and according to some authors it has been hidden by the art of the great genius. A fascinating tour of the epistemological studies of this prodigious Renaissance man is made from his manuscripts, codes, sketches and historical, biographical and pictorial works. Describe your ontology: study of nature, man and the universe, his study of living, psychic and social systems and the empirical approach: experiential and experimental epistemology. © 2020, Universidad del Zulia. All rights reserved.